2020
DOI: 10.2967/jnumed.119.241174
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting Metastatic Disease in 68Ga-PSMA-11 PET–Positive Osseous Lesions in Prostate Cancer

Abstract: Bone is the most common site of distant metastatic spread in prostate adenocarcinoma. Prostatespecific membrane antigen uptake has been described in both benign and malignant bone lesions, which can lead to false-positive findings on 68 Ga-prostate-specific membrane antigen-11 positron emission tomography (68 Ga-PSMA-11 PET). The purpose of this study was to evaluate the diagnostic accuracy of 68 Ga-PSMA-11 PET for osseous prostate cancer metastases and improve bone uptake interpretation using semi-quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 33 publications
(34 reference statements)
2
20
0
Order By: Relevance
“…Data on the significance of these indeterminate lesions on staging PSMA-targeted imaging are lacking. Several systems have been proposed to facilitate the interpretation of PSMA-targeted PET scans [30][31][32][33]. These systems allow for better communication between nuclear physicians and referring clinicians and offer a standardized classification scheme of equivocal findings to guide further management.…”
Section: Introductionmentioning
confidence: 99%
“…Data on the significance of these indeterminate lesions on staging PSMA-targeted imaging are lacking. Several systems have been proposed to facilitate the interpretation of PSMA-targeted PET scans [30][31][32][33]. These systems allow for better communication between nuclear physicians and referring clinicians and offer a standardized classification scheme of equivocal findings to guide further management.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, their study also showed that SUVmax was related to bone disease progression. Le et al ( 27 ) showed that the differential of malignant bone metastases also achieved satisfactory diagnostic performance based on the factor of PSMA-RADS rating, SUVmax, and SUVmax ratio of the lesion to blood pool by 68Ga-PSMA-11 PET/CT image. In fact, SUVmax only reflects the metabolic information of the tumor within a single pixel in the image and cannot quantify the spatial heterogeneity of the overall metabolic distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Two interpretative schemes that serve as models for structured reports have been proposed for diagnostic PSMA PET-CT, including a system proposed by a single institution (Johns Hopkins University) ( Table 7 ) [ 89 ] and a system used in the PROMISE trial ( Table 8 ) [ 90 ]. For [ 68 Ga]-PSMA identification of bone metastases, it has been additionally proposed that positive lesions be defined as having a lesion:normal tissue SUVmax ratio of 2.2 for blood pool and 4.1 for normal bone [ 91 ]. However, neither these indices nor the structured reporting classifications have been prospectively and independently validated in large series and, at this point, are best regarded as consensus recommendations.…”
Section: Urological Malignanciesmentioning
confidence: 99%